2015
DOI: 10.1096/fj.15-277673
|View full text |Cite
|
Sign up to set email alerts
|

Occludin controls HIV transcription in brain pericytes via regulation of SIRT‐1 activation

Abstract: HIV invades the brain early after infection; however, its interactions with the cells of the blood-brain barrier (BBB) remain poorly understood. Our goal was to evaluate the role of occludin, one of the tight junction proteins that regulate BBB functions in HIV infection of BBB pericytes. We provide evidence that occludin levels largely control the metabolic responses of human pericytes to HIV. Occludin in BBB pericytes decreased by 10% during the first 48 h after HIV infection, correlating with increased nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(108 citation statements)
references
References 37 publications
(54 reference statements)
3
105
0
Order By: Relevance
“…However, intriguing new evidence showed that occludin could largely control metabolic responses of human pericytes infected with HIV-1. 134 Along with this data, is preliminary proteomic analysis of occludin and claudin-4 in epithelial cells, which showed a close association of these proteins with trafficking, signaling and endocytotic pathways. 135 Thus, the redistribution of junction proteins may not only affect barrier physical properties directly but it may further modulate ongoing signaling processes enhancing BBB dysfunction.…”
mentioning
confidence: 55%
“…However, intriguing new evidence showed that occludin could largely control metabolic responses of human pericytes infected with HIV-1. 134 Along with this data, is preliminary proteomic analysis of occludin and claudin-4 in epithelial cells, which showed a close association of these proteins with trafficking, signaling and endocytotic pathways. 135 Thus, the redistribution of junction proteins may not only affect barrier physical properties directly but it may further modulate ongoing signaling processes enhancing BBB dysfunction.…”
mentioning
confidence: 55%
“…We recently explored the relationship between occludin and metabolic alterations in pericytes following HIV infection and showed that occludin impairs viral proliferation. 25 This wide range of metabolic effects could be achieved if occludin was partnered with integrative metabolic players like AMPK and SIRT-1. Both influence gene expression, activation of transcription factors, glucose metabolism and cellular energetics, 28,59,60 and our current and previous 25 findings strongly indicate the existence of a metabolic regulatory triad: OCCLUDIN-AMPK-SIRT1 ( Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…25 This wide range of metabolic effects could be achieved if occludin was partnered with integrative metabolic players like AMPK and SIRT-1. Both influence gene expression, activation of transcription factors, glucose metabolism and cellular energetics, 28,59,60 and our current and previous 25 findings strongly indicate the existence of a metabolic regulatory triad: OCCLUDIN-AMPK-SIRT1 ( Figure 7). This triple partnership is exemplified by our findings showing that pericytes become sensitive to insulin and enhance their glucose uptake in an AMPK-dependent manner when occludin levels are elevated, which is consistent with the involvement of SIRT1 and AMPK in regulation of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for Sirt-1 in the brain has been proposed, in controlling blood brain barrier proteins and HIV infection in pericytes (Castro et al 2016). On the other hand, a potential ability of microglial Sirt-1 to control the onset of cognitive decline by affecting microglia and brain inflammatory components has been observed (Chen et al 2005; Cho et al 2015).…”
Section: Discussionmentioning
confidence: 99%